Study of early age stiffness development in lime-cement blended mortars - Ramesh, Meera (2019)
Lime-cement blended mortars are frequently used in building conservation, as well as in new masonry constructions. Since mortar plays an important role in governing the non-linear behavior and global performance of masonry from the earliest moments of construction, this work intends to study the evolution of its elastic modulus from very early ages. The development of stiffness in blended mortars has been studied using a recently developed approach called EMM-ARM (Elasticity Modulus Monitoring through Ambient Response Method). The method is based on continuous modal identification of the first flexural resonant frequency of composite beams that contain the material to be tested. The evolution of resonant frequency identified during the experiment can be directly correlated with the Young’s modulus by using the dynamic equation of motion. The experimental program involves validation of the applicability of EMM-ARM in blended mortars by comparison with results from conventional static method of cyclic compression according to EN 12390-13. Three distinct blended mortars (with target workability of 175 mm) with 33%, 50% and 66.67% lime in binder and 1:3 binder aggregate ratio, by volume, have been studied. The evolution of Young’s modulus will permit discussion on interaction of binders involved in the mixes. Such a study will also make it possible to explore the consequences of the observed kinetics of stiffness evolution on the stress development within masonry structures since the early ages of application of the mortar interface